ROAD: The directory of open access scholarly resources to promote open access worldwide - Cornic, Nathalie (2016)
ROAD, the Directory of Open Access scholarly Resources, is a new service implemented by the ISSN International Centre. ROAD provides a free access to a selection of worldwide, multidisciplinary scholarly resources in open access that have been identified by the ISSN Network. This paper will present ROAD background, its innovative concept and how it is positioned in the open access ecosystem.
t.ly/VOHF
Keywords: Open access; Shloarly resources; Serial publication; ISSN